A geospatial framework to support integrated biogeochemical modelling in the United Kingdom. (June 2015) - Greene, S.; Johnes, P.J.; Bloomfield, J.P.; Reaney, S.M.; Lawley, R.; Elkhatib, Y.; Freer, J.; Odoni, N.; Macleod, C.J.A.; Percy, B.
Abstract: Anthropogenic impacts on the aquatic environment, especially in the context of nutrients, provide a major challenge for water resource management. The heterogeneous nature of policy relevant management units (e.g. catchments), in terms of environmental controls on nutrient source and transport, leads to the need for holistic management. However, current strategies are limited by current understanding and knowledge that is transferable between spatial scales and landscape typologies. This study presents a spatially-explicit framework to support the modelling of nutrients from land to water, encompassing environmental and spatial complexities. The framework recognises nine homogeneous landscape units, distinct in terms of sensitivity of nutrient losses to waterbodies. The functionality of the framework is demonstrated by supporting an exemplar nutrient model, applied within the Environmental Virtual Observatory pilot (EVOp) cloud cyber-infrastructure. We demonstrate scope for the use of the framework as a management decision support tool and for further development of integrated biogeochemical modelling. Highlights: High resolution geospatial biogeochemical framework for modelling nutrient flux. Nitrogen and phosphorus modeled across many spatial scales in the United Kingdom. Upscales from grid to river catchment, regional and national scale. Knowledge transfer from data-rich research catchments to data-poor areas. Many other biogeochemical models can be fit to the framework.